How COVID-19 case fatality rates have shaped perceptions and travel intention?. (June 2021) - Rastegar, Raymond; Seyfi, Siamak; Rasoolimanesh, S. Mostafa
Abstract: This study investigates the perceptions shaped by media towards trust, crisis management, healthcare system, and solidarity, as well as willingness to support and travel intention across two groups of countries with higher and lower COVID-19 case fatality rates. The findings showed more positive perceptions towards trust, crisis management, healthcare system, and solidarity in those countries with lower case fatality rate. The results also demonstrated the positive effects of trust and solidarity on willingness to support a destinations and indirect effects on travel intention for the countries with higher rate of case fatality. Theoretical and practical implications post pandemic are also discussed.